Cell fusion in health and disease II: cell fusion in disease - Dittmar, Thomas (Springer eBook., 2011)
Although cell fusion is an omnipresent process in life, to date considerably less is still known about the mechanisms and the molecules being involved in this biological phenomenon in higher organisms. In Cell Fusion in Health and Disease Vol 1 & Vol 2 leading experts will present up-to-date overviews about cell fusion in physiological and patho-physiological processes, which further covers the current knowledge about cell fusion-mediating molecules. Volume 1 deals with Cell Fusion in Health and will cover aspects of cell fusion in fertilization, placentation, in C. elegans, in skeletal muscle development and tissue repair, and the use of cell fusion for cellular reprogramming and cancer vaccine development. Volume 2 focuses on Cell Fusion in Disease with a particular emphasis on the role of cell fusion in cancer development and progression. Thus, Cell Fusion in Health and Disease Vol 1 & Vol 2 represents a state-of-the-art work for researchers, physicians or professionals being interested in the biological phenomenon of cell fusion and bey